Proteomics and N‐glycoproteomics analysis of an extracellular matrix‐based scaffold‐human treated dentin matrix. (7th May 2019) - Li, Jie; Yang, Hefeng; Lu, Qi; Chen, Duanjing; Zhou, Mengjiao; Kuang, Yunchun; Ying, Siqi; Song, Jinlin
Abstract: Extracellular matrix (ECM)‐based biomaterials developed from mammalian tissues have been successfully used in preclinical and clinical tissue engineering applications. We have previously reported about the applicability of dentin‐based scaffold, treated dentin matrix (TDM), for tooth root regeneration. However, TDM protein composition has not been characterized. Here, we used a shotgun proteomic strategy to profile human TDM proteome. N‐glycoproteins were enriched by lectin affinity chromatography and identified by mass spectrometry. The total human TDM proteome was compared with the previously published human dentin proteome, and bioinformatics analysis were performed accordingly. In total, 708 proteins were identified by mass spectrometry in human TDM, of which 208 were N‐glycoproteins with 318 identified glycosylation sites. Collagens, proteoglycans, small integrin‐binding ligand N‐linked glycoproteins (SIBLINGs), and growth factors, such as COL1A1, biglycan, dentin sialoprotein, and transforming growth factor beta 1, were identified. Glycoproteins were enriched in "biological processes" Gene Ontology terms such as cellular process, biological regulation, response to stimulus, metabolic process, immune system process, and biological adhesion. Thus, our comprehensive study of the human TDM proteome revealed that dentin proteins are more heterogeneous than previously documented. Our findings provide clues for designing new biomaterials for tooth root regeneration and understanding dentin formation.